Designing For Tomorrow:A Systematic Review of Organizational Design, Sustainability, and External Environment Dynamics - Munawaroh, Munawaroh; Widodo, Aris; Rahmattullah, Tiyo; Kelana, Jaka Putra; Karnain, Ahmad; Subroto, Desty (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Contemporary organizations today face unprecedented sustainability challenges amidst an increasingly volatile global environment characterized by climate change, geopolitical instability, and technological disruption. This situation demands a shift from traditional profit-maximizing models to sophisticated and adaptive organizational architectures that balance economic viability, environmental protection, and social justice. This research aims to fill this gap in the existing literature by synthesizing empirical evidence on the relationship between organizational design, sustainability integration, and external environmental dynamics. Using a Systematic Literature Review methodology, this study conducted an in-depth analysis of 22 selected peer-reviewed publications from 2020 to 2025. The findings of the thematic analysis revealed three critical themes: the urgent need for adaptive design in response to environmental volatility, the importance of embedding sustainability into organizational architecture, and the identification of key implementation barriers including structural rigidity, cultural resistance, and resource constraints. The study highlighted that traditional mechanistic structures often hinder the flexibility necessary for sustainability, while organic designs may lack implementation discipline. As a significant theoretical and practical contribution, this study proposes a new model called Dynamic Adaptation-Sustainability Integration (DASI). This three-dimensional framework recommends: (1) Structural Flexibility that enables rapid reconfiguration through modularity and decentralization; (2) Cultural Permeability that facilitates the internalization of sustainability values beyond mere ceremonial compliance; and (3) Environmental Scanning Capacity to proactively detect external threats and opportunities. In conclusion, organizations are encouraged to undertake parallel transformations in their structure, culture, and monitoring systems to create a resilient and sustainable organizational ecosystem in the face of global disruptions.